In silico-in vitro modeling to uncover cues involved in establishing microglia identity: TGF-β3 and laminin can drive microglia signature gene expression - Timmerman, Raissa; Zuiderwijk-Sick, Ella Alwine; Baron, Wia; Bajramovic, Jeffrey John (Frontiers in Cellular Neuroscience, 2023)
Microglia are the resident macrophages of the central nervous system (CNS) and a play key role in CNS development, homeostasis, and disease. Good in vitro models are indispensable to study their cellular biology, and although much progress has been made, in vitro cultures of primary microglia still only partially recapitulate the transcriptome of in vivo microglia. Here, we explored a combination of in silico and in vitro methodologies to gain insight into cues that are involved in the induction or maintenance of the ex vivo microglia reference transcriptome. First, we used the in silico tool NicheNet to investigate which (CNS-derived) cues could underlie the differences between the transcriptomes of ex vivo and in vitro microglia. Modeling on basis of gene products that were found to be upregulated in vitro, predicted that high mobility group box 2 (HMGB2)- and interleukin (IL)-1β-associated signaling pathways were driving their expression. Modeling on basis of gene products that were found to be downregulated in vitro, did not lead to predictions on the involvement of specific signaling pathways. This is consistent with the idea that in vivo microenvironmental cues that determine microglial identity are for most part of inhibitory nature. In a second approach, primary microglia were exposed to conditioned medium from different CNS cell types. Conditioned medium from spheres composed of microglia, oligodendrocytes, and radial glia, increased the mRNA expression levels of the microglia signature gene P2RY12. NicheNet analyses of ligands expressed by oligodendrocytes and radial glia predicted TGF-β3 and LAMA2 as drivers of microglia signature gene expression. In a third approach, we exposed microglia to TGF-β3 and laminin. Exposure to TGF-β3 increased the mRNA expression levels of the microglia signature gene TREM2. Microglia cultured on laminin-coated substrates were characterized by reduced mRNA expression levels of extracellular matrix-associated genes MMP3 and MMP7, and by increased mRNA expression levels of the microglia signature genes GPR34 and P2RY13. Together, our results suggest to explore inhibition of HMGB2- and IL-1β-associated pathways in in vitro microglia. In addition, exposure to TGF-β3 and cultivation on laminin-coated substrates are suggested as potential improvements to current in vitro microglia culture protocols.